The holiday honeymoon switch ebook - McKay, Julia (2024)
Trading places and vacations might just be the Christmas miracle these two best friends need “ The Holiday meets The Unhoneymooners in this friends-swapping-places romance that has it all: mistletoe and make-outs, plus sun, sand, and swoon!”—Chantel Guertin, author of It Happened One Christmas Holly Beech and Ivy Casey are bury-the-body besties. They’re so in sync, they even look alike. When Holly’s fiancé jilts her, leaving her in shock and with a nonrefundable honeymoon, Holly convinces Ivy to switch places. Ivy will go on the Hawaiian honeymoon her best friend can’t bear to take alone, while Holly escapes to Ivy’s rented Hudson Valley cabin to binge-watch holiday movies and heal.     But Holly’s wallowing is interrupted when her rugged Airbnb host turns out to be her high school academic rival who’s had a major glow-up. Meanwhile, Ivy’s (now Hawaiian) annual solo art retreat is upended when Holly’s ex-fiancé checks into the honeymoon suite—with a new woman. Raging and bed-less, the last thing Ivy expects is for the hot hotel bartender to come to her rescue. Against all odds, this Christmas might prove the most magical yet.